Current Business Process Improvement in PT Vidio Dot Com - Shella Shella; Arwina Karmudiandri; Irwanto Handojo (Jurnal Abdimas Sosial, Ekonomi, dan Teknologi, 2022)
Merdeka Belajar – Kampus Merdeka (MBKM) is a government program to improve student’s leadership skills, innovation, capacity, personality, and independence. In this era of globalization, competition becomes more challenging especially in the workplace. Therefore, students need to prepare themselves by participating this MBKM program. This MBKM program was held at PT Vidio Dot Com, a broadcasting company and number one OTT in Indonesia, as a business analyst. The primary work and responsibility a business analyst is improvement project. This project is used to improve current business process held and build neat documentation in all divisions at PT Vidio Dot Com. All MBKM activities are effective and efficient to be conducted. Students can to learn, apply, and obtain several achievements in attitude, knowledge, general skills and special skills. This MBKM program is very feasible to run by the government which students can maximize the time given to increase their abilities and achieve the goal set by the company. Even though there are several limitations and need to be improved, this program also contribute to company and society.